Gastrointestinal delivery of codfish skin-derived collagen hydrolysates:deep eutectic solvent extraction and bioactivity analysis - Silva, Isa; Vaz, Bárbara M. C.; Sousa, Sérgio; Pintado, Maria Manuela; Coscueta, Ezequiel R.; Ventura, Sónia P. M. (Food Research International, 2024)
The fishing industry produces substantial by-products, such as heads, skins, bones, and scales, rich in collagen—a prevalent protein in these materials. However, further application of deep eutectic solvent-based extraction remains unexplored. In this study, we extracted collagen with urea: propanoic acid mixture (U:PA; 1:2) with a 2.2% yield, followed by enzymatic hydrolysis with alcalase for 120 min. The resulting bioactive peptides demonstrated notable antioxidant activity (961 µmol TE) and antihypertensive properties (39.3% ACE inhibition). Subsequently, we encapsulated 39.3% of these hydrolysates in chitosan-TPP capsules, which released about 58% of their content, primarily in the intestine, as mimicked in the in vitro model of the gastrointestinal tract. Although the digestion process did not significantly alter the size of the non-encapsulated collagen peptides, it did influence their health benefits. The promising results suggest that further research could optimize the use of collagen from fish by-products, potentially offering a sustainable source for health products.